Evaluation of Fungal Growth on Olive-Mill Wastewaters Treated at High Temperature and by High-Pressure Homogenization - Cibelli, Francesca; Bevilacqua, Antonio; Raimondo, Maria L.; Campaniello, Daniela; Carlucci, Antonia; Ciccarone, Claudio; Sinigaglia, Milena; Corbo, Maria R. (Frontiers in Microbiology, 2017)
Reuse of olive mill wastewaters (OMWWs) in agriculture represents a signiﬁcant challenge for health and safety of our planet. Phytotoxic compounds in OMWW generally prohibit use of untreated OMWWs for agricultural irrigation or direct discharge into surface waters. However, pretreated OMWW can have positive effects on chemical and microbiological soil characteristics, to fight against fungal soil-borne pathogens. Low amounts of OMWW following thermal (TT-OMWW) and high-pressure homogenization (HPH-OMWW) pretreatments counteracted growth of some of 12 soil-borne and/or pathogenic fungi examined. With fungal growth measured as standardized change in time to half maximum colony diameter, Δτ, overall, HPH-OMWW showed increased bioactivity, as increased mean Δτ from 3.0 to 4.8 days. Principal component analysis highlighted two fungal groups: Colletotrichum gloeosporioides , Alternaria alternata, Sclerotium rolfsii, and Rosellinia necatrix, with growth strongly inhibited by the treated OMWWs; and Aspergillus ochraceus and Phaeoacremonium parasiticum, with stimulated growth by the treated OMWWs. As a non-thermal treatment, HPH-OMWW generally shows improved positive effects, which potentially arise from preservation of the phenols.